2006
DOI: 10.1007/s11259-006-3373-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Commercially Available Human Serum Amyloid A (SAA) Turbidimetric Immunoassay for Determination of Feline SAA Concentration

Abstract: Serum amyloid A (SAA) is an acute-phase protein in cats likely to be useful for diagnosing and monitoring inflammatory diseases, especially if rapid, reliable and automated assays can be made available. A commercially available automated human SAA turbidimetric immunoassay (SAA-TIA) was evaluated for determination of SAA in cats. Intra-assay and inter-assay imprecisions were in the ranges 2.1-9.9% and 7.0-12.5%, respectively, and without significant inaccuracy. Eighty-eight cats were divided into groups accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 14 publications
5
59
0
Order By: Relevance
“…In this study, values of SAA lower than the detection limit (DL) of the assay (0.38 μg/mL) were set as equal to DL for statistical analysis. It should be pointed out that this approach could have resulted in bias in the statistical results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, values of SAA lower than the detection limit (DL) of the assay (0.38 μg/mL) were set as equal to DL for statistical analysis. It should be pointed out that this approach could have resulted in bias in the statistical results.…”
Section: Discussionmentioning
confidence: 99%
“…SAA concentrations were determined by a human turbidimetric immunoassay (LZ‐SAA; Eiken Chemical Co., Tokyo, Japan) previously validated for use in cats . Serum Hp concentrations were determined by use of the haemoglobin‐binding method with the use of a commercial kit (Tridelta Development Ltd., Kildare, Ireland).…”
Section: Methodsmentioning
confidence: 99%
“…Most methods are timeconsuming, however, and relatively expensive, so limiting the wide-scale use of APPs in routine practice. Recently, immunoturbidimetric tests for measuring feline APPs have been validated (Bence et al, 2005;Hansen et al, 2006) and should probably reduce the cost per test, thus allowing greater use of APPs measurement.…”
Section: How To Measure Appsmentioning
confidence: 99%
“…In 2006, Hansen et al reported that the SAA concentration in cats could be measured using a commercially available turbidimetric immunoassay (TIA) designed for measuring human SAA [8]. The purposes of this study were to assess the applicability of human SAA-TIA to measurement of the feline SAA concentration by using recombinant feline SAA protein (rfSAA) and to evaluate the clinical usefulness of measuring the SAA concentration routinely in cats with various diseases.…”
mentioning
confidence: 99%